Culturally-Embedded Gamification: Integrating Behoa Valley Local Wisdom to Enhance Elementary Science Learning Outcomes - Marlene Juita Kadoi; Rizal Rizal; Surahman Wilade; Pahriadi Pahriadi; Sisriawan Lapasere (Journal of Innovation and Research in Primary Education, 2026)
Elementary science education often remains teacher-centered and disconnected from students' cultural contexts, resulting in low learning outcomes. This study aimed to improve fifth-grade students' learning outcomes in Natural and Social Sciences through a gamification model based on the local wisdom of Behoa Valley at Rompo Elementary School. Employing classroom action research following Kemmis and McTaggart's spiral model, the study involved 12 fifth-grade students across two cycles during October-November 2025. Data were collected through achievement tests, structured observations, and documentation, then analyzed using quantitative and qualitative approaches. The intervention integrated game elements (points, challenges, rewards) via Wordwall platform with place-based learning resources, specifically the Behoa Valley's megalithic sites, to teach earth science concepts. Student learning outcomes improved progressively from pre-test (average: 54.28, completion: 41.67%) through Cycle I (average: 73.33, completion: 66.67%) to Cycle II (average: 80.41, completion: 83.33%). Student and teacher activities achieved "very good" criteria, with engagement scores reaching 94.64% and 90% respectively in Cycle II. The culturally-embedded gamification model significantly improved student learning outcomes by creating meaningful connections between scientific concepts and familiar cultural landscapes. This approach demonstrates that integrating local wisdom with interactive pedagogy enhances both cognitive achievement and cultural identity, offering valuable implications for culturally-responsive STEM education in heritage-rich contexts.